Hospital-acquired viral respiratory infections in neonates hospitalized since birth in a tertiary neonatal intensive care unit - Poole, Claudette L. (J Perinatol, 2019)
OBJECTIVE: To determine frequency of hospital-acquired viral respiratory infections (HA-VRI) and associated outcomes in a NICU. STUDY DESIGN: Prospective cohort study conducted from 4 October 2016 to 21 March 2017. Infants hospitalized from birth in the NICU had a weekly nasal swab collected for testing using a multiplex PCR assay capable of detecting 16 different respiratory viruses. RESULTS: Seventy-four infants enrolled, with 5 (6.8%) testing positive for a virus (incidence rate of 1.3/1000 patient days). VRI positive infants had a younger gestational age (median 27 w vs. 32 w, p = 0.048); were hospitalized longer (97 d vs 43 d, p = 0.013); required more antibiotics (8 d vs. 4 d, p = 0.037) and were more likely to be diagnosed with bronchopulmonary dysplasia (p = 0.008) compared to VRI negative infants. CONCLUSION: Respiratory viruses are a frequent cause of HAI in the NICU and are associated with negative outcomes.